2008
DOI: 10.1093/intimm/dxn057
|View full text |Cite
|
Sign up to set email alerts
|

Four novel ULBP splice variants are ligands for human NKG2D

Abstract: UL16-binding proteins [ULBPs, also termed as retinoic acid early transcripts (RAET1) molecules] are frequently expressed by malignant transformed cells and stimulate anti-tumor immune responses mediated by NKG2D-positive NK cells, CD8(+) alphabeta T cells and gammadelta T cells in vitro and in vivo. In this study, we identified four novel functional splice variants of ULBPs including ULBP4-I, ULBP4-II, ULBP4-III and RAET1G3 in HepG2 liver carcinoma cells, WISH human amnion cells, Hep-2 larynx carcinoma cells a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 46 publications
2
20
0
Order By: Relevance
“…Instead, they can recognize non-peptide antigens, such as phosphoantigens 18 and stress-induced proteins such as MICA/B, 19 ULBPs, 20 heat shock proteins and F1F0-ATPase, 21 via TCR and/ or non-TCR receptors. In vitro and in vivo studies have demonstrated that human cd T cells can kill various haematological and solid tumour cells expressing these antigens.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, they can recognize non-peptide antigens, such as phosphoantigens 18 and stress-induced proteins such as MICA/B, 19 ULBPs, 20 heat shock proteins and F1F0-ATPase, 21 via TCR and/ or non-TCR receptors. In vitro and in vivo studies have demonstrated that human cd T cells can kill various haematological and solid tumour cells expressing these antigens.…”
Section: Discussionmentioning
confidence: 99%
“…Stable transfectant EL4-ULBP4 was selected in RPMI-1640 supplemented (Gibco BRL) with 1 mg/mL G418. The transfected cells were stained with anti-ULBP4 mAb 8C9 previously generated in our laboratory, 27,28 followed by FITC-conjugated sheep anti-mouse IgG (Zhongshan) and sorted by flow cytometry. T-lymphoma cell line (J.RT3-T3.5), deficient in both TCR ␣ and ␤ chains (ATCC), was cotransfected with full-length human peripheral blood mononuclear cell (PBMC)-derived ␥9 and ␦2 chain (http://imgt.cines.fr/, 29 sequence shown in Table 1) (CDR3␦ region was OT3 nucleotide acid sequence).…”
Section: Cell Lines and Transfectantsmentioning
confidence: 99%
“…In brief, a sequence encoding the extracellular domain of ULBP4 (aa 1-226) was amplified by polymerase chain reaction (PCR) using the primers U4f (5Ј-CGGAATTCATGCGAAGAATATCCCTGACTT-3Ј) and U4r (5Ј-GGCGGCCGCCTATTAGTGGTGGTGGTGGTGGTG-GTGGTGTCTAT CTGGTAGACTAGAAGAA-3Ј) from a previously cloned vector pET22b(ϩ)/ULBP4 26,27 and subcloned into the mammalian expression vector pEAK12, a kind gift from Dr Brian Seed (Massachusetts General Hospital and Harvard Medical School); the italicized portions of the sequences represent the restriction enzyme cutting site. Plasmid pEAK12/rULBP4 was stably transfected into HEK 293ET cells, and the fusion proteins were purified from culture supernatants using HisTrap kit (Amersham Pharmacia Biotech) following the instruction of the manufacturer.…”
Section: Construction and Expression Of Soluble Ulbp4mentioning
confidence: 99%
“…IFN-γ mediates NK cells’ cytolytic activity through the increase of the ULBP level of the tumors cells which then binds to the NKG2D [26]. Binding of RAET1G3 which is the variant of ULBPs expressed by HepG2 was found to stimulate NK cells to further enhance IFN-γ secretion [27]. This idea had raised the possibility that IFN-γ production stimulated by R. korthasii methanol extract might contribute to the activation of NK cells’ cytotoxicity against HepG2 and K562 [9-11].…”
Section: Discussionmentioning
confidence: 99%